以发热、关节炎、皮肤色素沉着为主要表现的血管免疫母细胞性T细胞淋巴瘤1例 (Beijing Da Xue Xue Bao Yi Xue Ban, 2020)
Angioimmunoblastic T-cell lymphoma is a rare T-cell lymphoma. The clinical manifestations are not specific. In addition to the common clinical manifestations of lymphomas such as fever, weight loss, night sweats and lymphadenopathy, it may also have skin rashes, arthritis, multiple serous effusions, eosinophilia and other systemic inflammatory or immune symptoms. The lymphoma cells of angioimmunoblastic T-cell lymphoma originates from follicular helper T cells, and the follicular structure of lymph nodes disappears. In the tumor microenvironment, in addition to tumor cells, there are a large number of over-activated immune cells, such as abnormally activated B cells, which produce a series of systemic inflammation or immune-related symptoms. This disease is rare and difficult to diagnose. This article reports a 36-year-old female. She got fever, joint swelling and pain, skin pigmentation, accompanied by hepatomegaly, splenomegaly, lymphadenopathy, anemia and other multiple-systems manifestations. The clinical manifestations of this patient were similar to autoimmune diseases such as adult onset Still's disease, rheumatoid arthritis, and systemic sclerosis, which made the diagnosis difficult. At the beginning of the disease course, the patient got arthritis and fever. And her white blood cells were significantly increased. Adult onset Still's disease should be considered, but her multiple-systems manifestations could not be explained by adult onset Still's disease. And her arthritis of hands should be distinguished with rheumatoid arthritis. However, the patient's joint swelling could get better within 3-7 days, and there was no synovitis and bone erosion on joint imaging examination. The rheumatoid factor and anti-CCP antibody were negative. The diagnostic evidence for rheumatoid arthritis was insufficient. The patient's skin pigmentation and punctate depigmentation were similar to those of systemic sclerosis. But the patient had no Raynaud's phenomenon, and her sclerosis-related antibody was negative. The diagnostic evidence for systemic sclerosis was also insufficient. After 3 years, she was finally diagnosed with angioimmunoblastic T-cell lymphoma by lymph node biopsy aspiration. This case suggests that the clinical manifestations of angioimmunoblastic T-cell lymphoma are diverse, and some symptoms similar to immune diseases may appear. When the patient's clinical symptoms are atypical and immune diseases cannot explain the patient's condition, and further evidence should be sought to confirm the diagnosis.